Steganography : random LSB insertion using discrete logarithm - Mohamed Amin, Muhalim; Salleh, Mazleena; Ibrahim, Subariah; Katmin, Mohd. Rozi (2003)
Due to advances in ICT, most of information are kept electronically. Consequently, the security of information has become a fundamental issue. Besides cryptography, steganography can be employed to secure information. Steganography is a technique of hiding information in digital media, whereby the message is embedded in a digital host before passing it through the network. Hence, the existence of the message is unknown. Besides hiding data for confidentiality, this approach of information hiding can be extended to copyright protection for digital media: audio, video, and images. In this paper, we proposed the Secure Information Hiding System (SIHS) that is based on Least Significant Bit (LSB) technique in hiding messages in an image. The system enhanced the LSB technique by randomly dispersing the bits of the message in the image and thus making it harder for unauthorized people to extract the original message. Discrete logarithm calculation technique is used for determining the location of the image pixels to embed the message. The proposed algorithm provides a stego-key that will be used during the embedding and extracting of the message.